2020
DOI: 10.1007/s10695-020-00875-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on the mercury sensitivity of zebrafish (Danio rerio) sperm

Abstract: The effect of age on the sensitivity of zebrafish sperm against mercury exposure was investigated in the present study. Although results of the use of sperm from mature individuals for toxicity tests have been published, there is no information about the exact age of the fish in some cases, which can affect the results. During the experiments, pooled sperm was stripped from males of 7, 12, or 18 months of age, divided into 5 sub-groups, diluted with different concentrations of Hg (0, 0.5, 1, 2.5, and 5 mg/L Hg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…In contrast, the LIN, VAP, VSL, and VCL reflect the trajectory characteristics of the sperm. 34,48 In this study, no significant effects were observed for the velocity of the average pathway (VAP) and curvilinear velocity (VCL) of zebrafish sperm in all of the TBPH exposure groups (Figure 2G and H). In contrast, after 6 h of exposure, zebrafish sperm showed significant decreases of the VSL and VCL in all TBPH exposed groups; VAP in all treatments except for 0.1 μM; the progressive motility in 1 μM, 10 μM, and 60 μM TBPH treatments; and the total motility in 10 μM TBPH treatments.…”
Section: In Vitro and Ex Vivo Evidence For Disruptions On Male Reprod...mentioning
confidence: 59%
“…In contrast, the LIN, VAP, VSL, and VCL reflect the trajectory characteristics of the sperm. 34,48 In this study, no significant effects were observed for the velocity of the average pathway (VAP) and curvilinear velocity (VCL) of zebrafish sperm in all of the TBPH exposure groups (Figure 2G and H). In contrast, after 6 h of exposure, zebrafish sperm showed significant decreases of the VSL and VCL in all TBPH exposed groups; VAP in all treatments except for 0.1 μM; the progressive motility in 1 μM, 10 μM, and 60 μM TBPH treatments; and the total motility in 10 μM TBPH treatments.…”
Section: In Vitro and Ex Vivo Evidence For Disruptions On Male Reprod...mentioning
confidence: 59%
“…Dietrich et al [33] also reported decreased total motility below 50% and a significant reduction of VSL but not VCL in the semen of rainbow trout Oncorhynchus mykiss when they activated the sperm with inorganic-mercury-contaminated water (Hg 2+ , iHg) at 10,000 µg/L. Pataki et al [52] suggested that the total motility and VCL of zebrafish Danio rerio semen decreased when the sperm was activated with Hgcontaminated water between 500 and 5000 µg/L; however, they found that with older fish (7, 12, and 18 months) these parameters suffered more remarkable alterations. In the present study, the semen evaluated was extracted from bocachico breeders of the same age (24 months).…”
Section: Discussionmentioning
confidence: 98%